Edukasi Pentingnya Kesehatan Reproduksi Remaja pada Siswa SMA Negeri 6 Kendari - Ramadhani, Andi Rizky; Putri, Adinda Syakiba Marwan; Nurdesi, Waode Sitti; Johan, Annisa Dwi Ramadhani; Tuljanah, Rawia; Sasmita, Rista; Bahar, Hartati; Effendy, Devi Savitri; Muchtar, Febriana; Lestari, Hariati; Tosepu, Ramadhan (Pakis Journal Institute, 2025)
New cases of HIV sufferers continue to grow every year. In 2022, there was an increase in HIV/AIDS cases by 3.8% in adolescents in Indonesia from the previous year. According to the Ministry of Health, in the age range of 15-24 years, there are about 1,929 cases of HIV infection. 76% of the 91 AIDS cases in Southeast Sulawesi occurred at the age of 25-49 years. The purpose of this activity is to provide educational information to adolescents about reproductive health so that they are not involved in risky sexual relationships. This educational activity was conducted at SMA Negeri 6 Kendari in June 2025. 27 students at SMA Negeri 6 Kendari, as a sample group, were involved. The methods applied in this activity were a presentation and a health education game (Rank 1). The results showed that the average pre-test score was 85 (SD=16.09) and increased to 92 (SD=9.53) in the post-test. Paired-Samples T test results showed P-Valeu = 0.219 (α>0.05). Based on this, it shows that there is a difference in knowledge and understanding of reproductive health in 27 samples of SMA Negeri 6 Kendari students before and after the delivery of material (education).